Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more ➡
Standard view
Full view
of .
×
0 of .
Results for:
P. 1
1a 2009 Logarithm

1a 2009 Logarithm

Ratings:

4.0

(1)
|Views: 862|Likes:

Availability:

See More
See less

06/14/2009

pdf

text

original

LogarithmsIn this chapter you must be able to(i)understand the relationship between logarithms and indices, and usethe laws of logarithms (excluding change of base)(ii)understand the definition and properties of e
x
and ln x, including therelationship as inverse functions and their graphsRelationship between log and indicesLet
pxlogax
a p
==
;
qylogay
aq
==
q pq p
aa.axy
+
==

;
ylogxlogxylog
aaa
+=
q pq p
aaayx
==
;
ylogxlog yxlog
aaa
=
x
n
= (a
p
)
n
= a
p n
= log
a
x
n
= n log
a
x

log
a
a

= 1 ; log
a
1

= 0i)Express log
y x
3
in terms of log x and log y.
logy)

21(3logx
ii)Express
5231
log8log
as a single logarithm.
)(
log5
iii)Solve the equation
2)5(loglog
66
=++
x x
.
))acceptable9(notx4;(x
==
Graphs of e
x
and ln x
1

Note these two: (1)
xe
x
=
ln
(2)
xe
x
=
ln
1Solve for xi)e
x
- 2 - 3e
-x
= 0
)3ln(
=
x
ii)e
3t
+ 2e
t
= 3e
2t
)2ln,0(
=
x
yyy = e
x
y = ln x2

iii)- 2 ln x = b
)(
2
b
e x
=
iv)3 ln x – ½ ln x = 5
)(
2
e x
=
v)ln x = 2 ( ln 3 - ln 5 )
)x(
259
=
vi)a
k
– e
kx
= 0
)ln(
a x
=
vii)x
ln x
= e
),(
1
=
ee x
viii) 2 + 5 e
x4

= 3ix)- ln x =
50t
+ c x)ln x =
31
(ln 16 + 2 ln 2)
)4(
=
x
xi)a
x
= e
2x +1
xii)2 (ln 2x) = 1 + ln a
)(
21
ae x
±=
xiii)3
2x
= 4
2 – x
xiv)e
x
- 2e
— x
= 12Solve the following equations giving x correct to 3 significant figures.a)7
x
. 8
2x - 1
= 6.3
)642.0x(
=
b)3
2x
– 3
x +2
+ 8 = 0
)893.1;0x(

=
c)2
x
= 3d)3
x+1
= 18e)2
x
. 3
2x
= 5
)5568.0(
3Solve for xa)e
x
( 1 - 2x ) = 0
)(
21
=
x
b)e
-x
( 1 + x ) = 0
}1xpossible);not(0 xe{
==
c)xe
x
= e
x
1)xcancel;dont
=
(
d)e
x
- e
-x
= 6 (1.818)4By using a suitable substitution, solve the following equations:a)2
2x
- 5 . 2
x
+ 6 = 0
)1x1.5849; 2ln3lnx(
===
b)3
2x + 1
+ 3
2
= 3
x + 3
+ 3
x
)(
2x;1x
==
5
If y = ln ( 1 + 6x + 8x
2
) - ln ( 1 + 5x + 4x
2
) + ln ( 1+ x )- ln (1 + 2x ),prove that y is independent of x.6 Solve for x and y :a) x - y = 1 ; 2
x
. 3
y
= 432
3